Independent Emergence of Yersinia ruckeri Biotype 2 in the United States and Europe - Welch, Timothy J. (American Society for Microbiology, 2011)

(untitled)
Biotype 2 (BT2) variants of the bacterium Yersinia ruckeri are an increasing disease problem in U.S. and European aquaculture and have been characterized as serovar 1 isolates that lack both peritrichous flagella and secreted phospholipase activity. The emergence of this biotype has been associated with an increased frequency of enteric redmouth disease (ERM) outbreaks in previously vaccinated salmonid fish. In this study, four independent specific natural mutations that cause the loss of both motility and secreted lipase activity were identified in BT2 strains from the United States, United Kingdom, and mainland Europe. Each of these was a unique mutation in either fliR, flhA, or flhB, all of which are genes predicted to encode essential components of the flagellar secretion apparatus. Our results demonstrate the existence of independent mutations leading to the BT2 phenotype; thus, this phenotype has emerged separately at least four times. In addition, BT2 strains from the United Kingdom were shown to have the same mutant allele found in U.S. BT2 strains, suggesting a common origin of this BT2 lineage. This differentiation of distinct BT2 lineages is of critical importance for the development and validation of alternative vaccines or other treatment strategies intended for the control of BT2 strains.